Resistance to Mycobacterium tuberculosis H37Rv infection induced by Listeria and mycobacterial lipids - Mára, M; Průchová, J; John, C; Smerák, P; Sír, Z (Folia microbiologica, 1981)
The avirulent strain Listeria monocytogenes (Welshimer) induced upon a single injection 4 weeks prior to challenge with Mycobacterium tuberculosis H37Rv resistance in guinea-pigs, which was manifested by a significant decrease of spleen weight and Feldman's index in immunized animals. The degree of resistance was dependent on the immunizing dose and time of administration. Repeated high doses of Listeria yielded only a low or no effect. Further increase of resistance was obtained using the BCG lipids; however, stimulation of resistance with listeria lipids was not successful and, finally, Freund's incomplete adjuvant was significantly effective in the Feldman index only. The BCG lipids, extracted with ethanol, which contained nitrogen and water-soluble substances, induced a significant resistance against M. tuberculosis infection. The chloroform-methanol BCG lipids were also effective, however, significantly less than the ethanol-extracted material. The listeria factor Ei itself or together with Freund's incomplete adjuvant possessed only low effectiveness against mycobacterial infection. However, if injected together with ethanol-extracted BCG lipids, it produced a significant degree of resistance which was higher than that induced by lipids only. The degree of resistance was comparable with the effect of living BCG strain which served as a source of isolated lipids.
Keywords: morčata; Listeria monocytogenes; imunizace; Freund's Adjuvant; Spleen; velikost orgánu; Mycobacterium bovis; Lipids; lipidy; Freundovo adjuvans; tuberkulóza; Animals; Tuberculosis; slezina; Immunization; Guinea Pigs; Organ Size; zvířata